2014
DOI: 10.1371/journal.pone.0093019
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Profile of the Renal Transcriptome of HIV-1 Transgenic Mice during Disease Progression

Abstract: Profiling of temporal changes of gene expression in the same kidney over the course of renal disease progression is challenging because repeat renal biopsies are rarely indicated in clinical practice. Here, we profiled the temporal change in renal transcriptome of HIV-1 transgenic mice (Tg26), an animal model for human HIV-associated nephropathy (HIVAN), and their littermates at three different time points (4, 8, and 12 weeks of age) representing early, middle, and late stages of renal disease by serial kidney… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Discrepancies between the mRNA expression profiles of the current study and previous studies are likely due to a number of limitations. For example, the IPAH RNA and protein profiles fluctuate markedly during disease progression ( 31 , 32 ), leading to variable RNA profiles. In addition, different detection platforms may have substantial impact on the profiling results and thus, subsequent experimental verification is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Discrepancies between the mRNA expression profiles of the current study and previous studies are likely due to a number of limitations. For example, the IPAH RNA and protein profiles fluctuate markedly during disease progression ( 31 , 32 ), leading to variable RNA profiles. In addition, different detection platforms may have substantial impact on the profiling results and thus, subsequent experimental verification is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, specimens were washed three times with PBS and incubated in a 1:1000-diluted secondary antibody (goat anti mouse IgG, Thermo, Grand Island, NY) for 2 hours at room temperature. Positive staining was revealed using peroxidase-labeled streptavidin and a diaminobenzidine substrate[ 16 ]. For determination of immunohistochemistry staining, stained sections were imaged using the Image Analysis System (AxioVision 4, Carl Zeiss, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Like APOL1, UBD is up-regulated in response to proinflammatory stimuli including IFN-γ (8). In a mouse model of HIV-associated nephropathy, UBD is among the most up-regulated genes in the kidney (9). Previous studies have shown that intrarenal…”
mentioning
confidence: 99%